Infrared emission from the CF3+NO2 reaction - Oum, K; Hancock, G (1997)
The reaction of the CF3 radical with NO2 has been investigated by using time-resolved FTIR emission spectroscopy. Strong infrared emission has been attributed to products, CF2O and FNO, excited in the ν2 and ν1 modes, respectively. The direct one-step production pathway 1a is suggested as a major reaction channel: CF3 + NO2 → CF2O + FNO, ΔH°298 = -267 kJ mol-1 (1a); → CF2O + F + NO, ΔH°298 = -31 kJ mol-1 (1b). The rate constant for reaction 1 was measured to be (2.4 ± 0.5) × 10-11 cm3 molecule-1 s-1. The F atom formation pathway 1b is the minor channel: the relative branching ratio of reactions 1a and 1b was estimated as 1 : 0.015. The formation of the FON isomer formed via a five-center intermediate is discussed as a possible carrier of an unidentified emission band near 1880 cm-1. The CF3O + NO reaction was investigated by the same technique. Lower emission intensities from the same reaction products were observed, with proportionally less vibrational excitation in the CF2O product.